2018
DOI: 10.1177/2151459318765381
|View full text |Cite
|
Sign up to set email alerts
|

Cementless Stem for Femoral Neck Fractures in a Patient’s 10th Decade of Life: High Rate of Periprosthetic Fractures

Abstract: Background:Subsidence of cementless femoral stems in hemiarthroplasty (HA) and increased fracture rates are ongoing concerns of orthopedic surgeons when treating fractures in very old patients. Additionally, bone cement implantation syndrome may result in perioperative cardiac or pulmonary complications, especially in older patients, leading to morbidity and mortality. This study was performed to analyze possible subsidence and intraoperative fractures in a cohort of very old patients treated with cementless s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
1
5
1
Order By: Relevance
“…In our series, there are 4 of 37 cases (10.1%) with intraoperative nondisplaced calcar fracture managed successfully with cerclage cabling. This rate is more common than the 5.4% of intraoperative femoral fracture for uncemented primary THA reported by Berry [44] , but is consistent with the 7%-12% reported for arthroplasty for femoral neck fractures [45] , [46] , [47] . In contrast to other MIS techniques, the SuperPATH approach allows for calcar and subtrochanteric cerclage cable placement through a smaller secondary incision, making the treatment of intraoperative calcar fractures straightforward and without significant compromise of the capsule or short external rotators.…”
Section: Discussionsupporting
confidence: 87%
“…In our series, there are 4 of 37 cases (10.1%) with intraoperative nondisplaced calcar fracture managed successfully with cerclage cabling. This rate is more common than the 5.4% of intraoperative femoral fracture for uncemented primary THA reported by Berry [44] , but is consistent with the 7%-12% reported for arthroplasty for femoral neck fractures [45] , [46] , [47] . In contrast to other MIS techniques, the SuperPATH approach allows for calcar and subtrochanteric cerclage cable placement through a smaller secondary incision, making the treatment of intraoperative calcar fractures straightforward and without significant compromise of the capsule or short external rotators.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the patients in this study experienced <3mm subsidence in stem (78.2%). The mean of subsidence was 2.16mm (SD 3.4), which was lower than what was found in the previous study of 2.9mm (SD 2.7) 11 and 3.9mm (SD 2) 8 . This result could be affected by the greater cortical thickness and higher volumetric bone mineral density (BMD) in Asia patients than white patients 13 .…”
Section: Discussioncontrasting
confidence: 79%
“…Two previous studies about cementless hemiarthroplasty in femoral neck patients found different results. Kabelitz et al 8 found 12% intra-operative fractures and a low subsidence rate (5%). Furthermore, a study by Choi et al found no subsidence 6 .…”
Section: Introductionmentioning
confidence: 96%
“…In all cases, we documented bone- or implant-related complications, including i) revision hip surgery for any cause with or without revision arthroplasty, ii) radiographic loosening/subsidence of the stem over 5 mm26), iii) dislocation of the HA head, iv) intraoperative fracture—defined as any fracture in the ipsilateral femoral bone recognized during surgery or on radiography immediately after the surgery, v) postoperative peri-prosthetic fracture, and vi) contralateral hip fracture. We also included surviving patients who were followed-up 10 years after the index surgery in the assessment of their functional states for pain, ambulation (bedridden, wheelchair, walker, cane, or without any aid), and residence (home, nursing facility, or hospital) as outcome measures.…”
Section: Methodsmentioning
confidence: 99%